Age and learning during unemployment - Niessen, Cornelia (Journal of Organizational Behavior, 2006)
This study investigated age, past job control, social support and financial hardship as predictors of continuous learning among a sample of unemployed job seekers. A total of 172 participants completed measures of continuous learning (motivation to learn, education initiative and updating behaviour) and of potential predictors. Analysis showed that age was not related to motivation to learn and education initiative. Past job control and social support moderated the relationship between age and continuous learning. Age was positively related to some types of continuous learning for unemployed people with high social support and high past job control. Future research should identify more individual and situational characteristics, which support continuous learning throughout the lifespan. Copyright © 2006 John Wiley & Sons, Ltd.